PRODUCTION AND PURIFICATION OF EXTRA CELLULAR LIPASE FROM PSEUDOMONAS CEPACIA AND STUDY THE PARTIALCHARACTERIZATION - Abdelhameed, Alyaa Maan; Khudair, Mohammed KH.; Farmman, Minna S. (Diyala Agricultural Sciences Journal, 2013)
Twelve isolates of Pseudomonas were obtained from thirty five(34%) from different species soil ,plants and river s water in al Muqdadia fields .Ability of lipase production by these isolates was screened Pseudomonas P5 was highest lipase producer identified as Pseudomonas cepacia . Lipase production conditions were studied .the highest production of lipase was observed when mineral medium containing 5% linseed oil inculcated with bacterial cells e ,ph 7.5 and incubated at40 c in shaking incubator120 r.p.m for 18 hr. Lipase was purified from bacterial cells by two steps including precipitation with ammonium sulfate and Ion exchange chromatography by DEAE- Sephadex-A25, fold of purification was 35 Uwith 36.5% enzyme recovery . The effect of some metal ions on lipase activity was studied .The Ca+2 increased lipase activity to 150%. The effect of specific substances on enzyme activity was investigated ,The result showed that Tween80 raised lipase activity to 145%.